Molecular characteristics of a novel strain of canine minute virus associated with hepatitis in a dog - Choi, Jeong-Won (Arch Virol, 2016)
A 5-year-old female Yorkshire terrier dog died a few days following hernia and ovariohysterectomy surgeries. Necropsy performed on the dog revealed that the surgeries were not the cause of death; however, degenerative viral hepatitis, showing intranuclear inclusion bodies in hepatic cells, was observed in histopathologic examination. Several diagnostic methods were used to screen for the cause of disease, and minute virus of canines (MVC) was detected in all parenchymal organs, including the liver. Other pathogens that may cause degenerative viral hepatitis were not found. Infection with MVC was confirmed by in situ hybridization, which revealed the presence of MVC nucleic acid in the liver tissue of the dog. Through sequencing and phylogenetic analysis of the nearly complete genome sequence, the strain was found to be distinct from other previously reported MVC strains. These results indicate that this novel MVC strain might be related to degenerative viral hepatitis in dogs.